Energy supply and the expansion of groundwater irrigation in the Indus-Ganges Basin - Scott, Christopher A.; Sharma, Bharat R. (2009)
Irrigation using groundwater has expanded rapidly in South Asia since the inception of the Green Revolution in the 1970s. Groundwater currently represents the largest source of irrigation in the Indus-Ganges Basin (IGB), which feeds over one billion people and provides direct livelihoods for hundreds of millions of farmers. Although abundant in absolute terms, groundwater is overexploited in the western IGB plains and is underutilized in the east. The spatial and temporal patterns of groundwater development are the result of multiple demand factors: (a) farmer investment, (b) subsidies and markets, and (c) population density; as well as supply factors: (d) sources of groundwater recharge, and (e) energy supply and pricing. This paper examines trends in electricity supply and groundwater development in the Indian portion of the IGB over the 1980 - 1999 period, with contextual reference to groundwater irrigation in Pakistan, Nepal, and Bangladesh. Principal findings include early-1980s' growth in numbers of electric pumps across the Indian IGB followed by 1990s' stagnation in the eastern part of the basin; this trend is linked to electricity supply and pricing policies, which have varied markedly from state to state. The eastern IGB presents an energy-groundwater paradox: a region rich in energy sources but with inadequate electricity supply that has led to increased reliance on diesel power, which in turn is limiting development of groundwater - one of this region's most abundant and agriculturally productive resources.